1993
DOI: 10.1111/j.1752-0606.1993.tb00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Problem Families and the Circumplex Model: Observational Assessment Using the Clinical Rating Scale (Crs)

Abstract: The validity, reliability, and curvilinearity of the Clinical Rating Scale (CRS) from the Circumplex Model were evaluated and the ability of the scale to discriminate between proble/clinical families and nonclinical families was tested on family cohesion, family adaptability, and family communication. Two groups of problem families were compared with two control groups. The study tested the main curvilinear hypothesis of the Circumplex Model that nonclinical families will have more Balanced system types than p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 17 publications
(18 reference statements)
3
53
0
1
Order By: Relevance
“…(Epstein, Bishop, & Levin, 1978). Functional families are able to provide support to their members, whereas dysfunctional families are less well equipped to do so (Thomas & Olson, 1993). Furthermore, functional families make adjustments to the family system to meet the demands of ill family members (Segrin & Flora, 2011), such as increasing problem-solving behaviours and showing more affective responses (Segrin & Flora, 2011;Wamboldt & Wamboldt, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…(Epstein, Bishop, & Levin, 1978). Functional families are able to provide support to their members, whereas dysfunctional families are less well equipped to do so (Thomas & Olson, 1993). Furthermore, functional families make adjustments to the family system to meet the demands of ill family members (Segrin & Flora, 2011), such as increasing problem-solving behaviours and showing more affective responses (Segrin & Flora, 2011;Wamboldt & Wamboldt, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…When compared to nonclinical families in other studies employing the CRS (see Thomas & Olson, 1993), both groups in this study communicated relatively well. However, couples who had increased their level of adoption openness tended to demonstrate higher communication skills than those who were not making changes.…”
Section: Were Really Happy With Adoption" Another Example Of Incongrmentioning
confidence: 70%
“…All three CRS dimensions have demonstrated excellent ability to discriminate between nonproblem and problem families. For a complete discussion of the reliability and validity of each dimension, see Thomas and Olson (1993). CRS ratings of couples' communication facility were derived from coders' listening to audiotapes of couples' interviews while following a printed verbatim copy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, family researchers conceptualized communication and decision making as integral to family functioning (Thomas & Olson, 1993). Other researchers found that communication Sebern 3 (Pruchno, Burant, & Peters, 1997a) and decision making (Deimling, Smerglia, & Schaefer, 2001) affected caregiver outcomes such as mood, depression, and well-being.…”
Section: Conceptual Frameworkmentioning
confidence: 99%